Teaching Writing Through Story Map to the Eighth Grade Students of State Junior High School 3 of Palembang - Uzer, Yuspar (Lembaga Penelitian STKIP PGRI Bandar Lampung, 2017)
The population of this research is the eighth grade students of State Junior High School 3 of Palembang consisted of 231 students. a convenience sample is a group of ndividuals who (conveniently) are available for study for VIII.4 consisted 37 students. Finally, the data finding in the pre-test was 77.22, after the treatment being conducted and the written test as in the post-test had been repeated, the students score was 79.9. Based on the calculation of the match t-test was higher than the critical of t value the data showed that the calculation of the match t-test was 6.56. It means that the null hypothesis was rejected and consequently alternative hypothesis was accepted. In other words teaching writing through story map to the eighth grade students of state junior high school 3 of Palembang was effective toincrease the studentsâ writing.